The little book of restorative justice : a bestselling book by one of the founders of the movement - Zehr, Howard (2014)
"The seminal work on Restorative Justice by one of the founders of the movement, now fully revised and updated. In a time of bitter differences and deep division, how should we as a society respond to wrongdoing? When a crime occurs or an injustice is done, what needs to happen? What does justice require? Howard Zehr is the father of Restorative Justice and is known worldwide for his pioneering work in transforming understandings of justice. Here he proposes workable Principles and Practices for making Restorative Justice possible in this revised and updated edition of his bestselling, seminal book on the movement. Our legal system's approach to justice has some important strengths, but also some deep failings. Victims, offenders, and community members often feel that justice does not adequately meet their needs. Justice professionals--judges, lawyers, prosecutors, probation and parole officers, prison staff--are frustrated with the system's shortcomings, too. Many feel that the process of justice deepens the wounds and conflicts in our society rather than bringing healing and peace. Restorative Justice, with its emphasis on identifying the justice needs of everyone involved in a crime, is a worldwide movement of growing influence that is helping victims and communities heal, while holding criminals accountable for their actions. This is not a soft-on-crime, feel-good philosophy, but rather a concrete effort to bring justice and healing to everyone involved in a crime. In The Little Book of Restorative Justice, Zehr first explores how restorative justice is different from criminal justice. Then, before letting those appealing observations drift out of reach into theoretical space, Zehr presents Restorative Justice Practices. Zehr undertakes a massive and complex subject and puts it in graspable form, without reducing or trivializing it. This is a handbook, a vehicle for moving our society toward healing and wholeness. This is a sourcebook, a starting point for handling brokenness with hard work and hope. This resource is also suitable for academic classes and workshops, for conferences and trainings, as well as for the layperson interested in understanding this innovative and influential movement"--
Includes bibliographical references.
Keywords: Restorative justice; Victims of crimes; Criminals -- Rehabilitation; Corrections -- Philosophy; Criminal justice, Administration of; LAW / Reference; LAW / Alternative Dispute Resolution